Antioxidant action of Rosemary extract in soybean oil submitted to thermoxidation - Ramalho, Valéria C. [UNESP]; Jorge, Neuza [UNESP] (My University, 2008)
This work was aimed at evaluating the antioxidant activity of rosemary extract added to soybean oil in thermoxidation conditions. Purified soybean oil, refined soybean oil and refined soybean oil containing 1,000 mg/kg rosemary extract were heated at 180°C. The oxidation of the samples was evaluated after 0, 2.5, 5, 7.5 and 10 hours of thermoxidation by means of oxidative stability determination, total polar compounds and conjugated dienes. The purified oil differed significantly from the refined oil, mainly in relation to oxidative stability due the removal of the natural antioxidants. Rosemary extract presented antioxidant effects at high temperatures. After 10 hours of heating, 1,000 mg/kg rosemary extract added to the refined soybean oil significantly increased the oil oxidative stability from 7.52 to 13.5 hours and decreased the formation of polymers and decomposing products measured through the polar rates from 17.35 to 7.99%. The build up of primary oxidation products gauged through diene rates also decreased from 1.61 to 0.80%. Rosemary extract could be recommended as an alternative antioxidant.
Keywords: Natural antioxidants; Rosmarinus officinalis; Soybean oil; Spices; Thermostability; Glycine max